Utilising potential field modelling to better inform on the 3D structural architecture in regions of excellent structural control. Issue 1 (1st December 2019) - Armit, Robin; Blaikie, Teagan; Betts, Peter; Ailleres, Laurent
Summary: Information in the third dimension is intrinsic to potential-field data. Potential-field interpretations and modelling can provide crucial regional and sub-surface geological constraints in areas considered to be structurally 'well' understood. These approaches should not be restricted to regions with little to no outcrop. The geophysical interpretation of the Leichhardt River Fault Trough provides new insight into the tectonic evolution of the region that was not apparent from the geological relationships alone. Evidence for a major inversion event over a larger region of the Western Fold Belt pre-dating ca. 1710 Ma. This requires a re-assessment of how we interpret the evolution of the eastern parts of the North Australian Craton. In the Mt Painter Inlier, geophysical inversion modelling indicates that significant additional Ordovician aged felsic intrusions occur at depth. The intrusion of this additional material in the Palaeozoic either could be the product of; or contributed to, an increased local geotherm and heat flow in the region during the Palaeozoic. There is a potential link between these intrusives and Palaeozoic hydrothermal mineralisation in the region (e.g. Mt Gee, Yudanamutana).